(untitled) (Journal of Asian Development Studies, 2025)
This study explored the relationship between Adverse Childhood Experiences (ACEs) and delinquent behaviour among students from Quetta. The predictive influence of ASCEs on later display of delinquent behaviours was also examined. The Adverse Childhood Experiences Scale (ACEs; Felitti & Vincent, 1990) and the Self-Reported Delinquency Scale (SRDS; Naqvi, 2007) were used to assess the study variables. The study followed a cross-sectional correlational design and collected data from 260 students (n=180 boys and n=79 girls) aged 16 to 21 years, selected via convenience sampling. The results showed a significant positive relationship between ACEs and delinquent behaviour. Regression analysis also showed that ACEs substantially predict delinquent behaviour among adolescents and young adults, explaining almost 40% of the variance in the delinquency scores. Demographic analyses indicated no substantial difference in gender for either variable. Considering age, the late adolescent group (18-19 years) displayed significantly higher scores than the early teenage group. The finding that childhood adversity may strongly affect youth behaviour stresses the need for trauma-informed educational and mental health practices for youth.